Manufacture and Prebiotic Potential of Xylooligosaccharides Derived From Eucalyptus nitens Wood - Míguez, Beatriz; Gullón, Patricia; Cotos-Yáñez, Tomás; Massot-Cladera, Malén; Pérez-Cano, Francisco José; Vila, Carlos; Alonso, José Luis (Frontiers in Chemical Engineering, 2021)
Mixtures of xylooligosaccharides (XOS) were manufactured from Eucalyptus nitens samples by hydrothermal processing. In order to obtain a product suitable to be used as a prebiotic, the liquors obtained were subjected to a refining sequence consisting of a two-step membrane filtration followed by anion exchange and freeze-drying. The process proposed allowed to obtain a highly refined product mainly made up of a mixture of substituted XOS with a degree of polymerization, DP3–10, which was evaluated for its prebiotic potential by in vitro fermentation assays. Their effects on the microbiota composition and the metabolic activity were assessed along the fermentation time and compared to fructooligosaccharides (FOS, a gold standard prebiotic), using fecal inocula from donors belonging to two age-groups (young and elderly). Significant and similar increases were observed in most of the bacterial groups considered (including Bifidobacterium spp. or several butyrate-producers) in both XOS and FOS in vitro interventions, although XOS resulted in significantly higher increases in total bacteria and lower rises in Clostridium clusters I and II than FOS. Regarding the metabolic activity, higher amounts of total organic acid (TOA; 150 vs. 110 mM) and higher total short-chain fatty acid (SCFA)/TOA ratio (0.88 vs. 0.70 mol/mol) were achieved at 28 h using XOS as a carbon source in comparison with FOS. Moreover, both substrates resulted in different metabolite profiles. Higher percentages of acetate and propionate were achieved when XOS were used as substrates, whereas FOS resulted in slightly higher concentrations of butyrate. No differences were found between both age-groups. Taking together these results, it can be concluded that XOS produced from E. nitens by a biorefinery-based approach led to, at least, similar prebiotic activity as that observed with FOS.